Open Legal Policy Peraturan Perundang-undangan Bidang Politik Dalam Putusan Mahkamah Konstitusi (Studi terhadap Putusan MK Bidang Politik Tahun 2015-2017) - Gardha Galang Mantara Sukma (Universitas Islam Indonesia, 2020)
This research comprises of two problem formulations: first, why does the Constitutional Court (MK) in six of its decisions asserts that the articles being tested are open legal policies? Second, what are the implications of the open legal policy in terms of the Constitutional Court decisions in the three legislations on politics? This is a juridical normative research with statutory and conceptual approach to regulations. The results of the research are: first, in two of the six decisions of the Constitutional Court, the basis of the consideration of the Constitutional Court is legal norms that are not regulated in details in the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), it can be deemed as open legal policy. Meanwhile, in the other four decisions of the Constitutional Court, open legal policy was not discussed explicitly but, in conclusion, the basis for asserting the articles reviewed were open legal policy because they were not regulated in details in the 1945 Constitution. Second, the implication of open legal policy of the Constitutional Court decisions in the three legislations on politics are: (1) reduced balance in the state structure, (2) lost opportunities to obtain justice in the social order. Suggestions given are that legislations on politics are easier to be incepted with group interests and pragmatic objectives, hence in examining legislations on politics that have open legal policy, the Constitutional Court must be more careful and courageous because it does not mean that the Constitutional Court cannot review it.